Employees’ transfer of training on job performance in an organization / Siti Noraini Mohd Tobi - Mohd Tobi, Siti Noraini (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Successful training programs may not guarantee that newly learned knowledge and skills are transferable to the workplace. This study aims to gain insight into some factors that determine the transfer of training and examines the relationship between five predictors: trainees’ characteristics, training design, work environment, trainers’ characteristics, and evaluation on employees’ job performance. Data for the study was collected from 100 support staff in INTAN, Bukit Kiara, Kuala Lumpur. The study found that trainees’ characteristics, training design, trainer’s characteristics, and evaluation have a positive and significant correlation on job performance. The result also showed that trainers’ characteristic is the most influential in training transfer. A future study is recommended to look into the post-training self-management context to understand the substantial role of training knowledge retention and its relationship between training transfer and job performance.